Black phosphorus/polydimethylsiloxane coated microfiber saturable absorber for ultrashort pulse fiber laser - Ng, Eng Khoon (2021)
Fiber lasers capable of generating ultrashort pulses have diverse applications in micromachining, medical science, and telecommunications. Ultrashort pulses generated from fiber lasers can be achieved through passive mode-locking via a saturable absorber (SA). Several black phosphorus (BP) fiber-based saturable absorbers have been reported with low damage thresholds, however, have poor repeatability for mass production due to uncontrollable deposition techniques. This research work focuses on a new technique to generate ultrashort pulses using optimized adiabatic tapered fiber saturable absorber with different dimensions of black phosphorus; vary from bulk to quantum dots. The experimental work was initiated with the optimization of bulk BP polymer composite based saturable absorbers of different taper profiles in erbium-doped fiber ring laser cavity. The BP polymer composite was prepared by dispersing BP powders in tetrahydrofuran solvent then adding in polydimethylsiloxane (PDMS) to form composite. The sonicated BP was observed in chunky pieces within micrometers, proven by the scanning electron microscope morphological characterization. The characteristics of BP, PDMS, and BP/PDMS composite were analyzed through Raman spectroscopy, field emission scanning electron microscope, and ultravioletvisible- near infrared absorption spectroscopy methods. A constant amount of BP polymer composite was deposited within the waist area of tapered fiber through spin coating method with optimized parameters; 4000 rpm for 6 minutes. The up/down transition and waist length were optimized with a waist diameter of 10 m was chosen as the constant parameter. Based on the experimental findings, the optimum taper profile was 30 mm of up/down transition length and 1 mm of waist length, which resulted in transmission loss of 3.34 dB, saturation fluence of 21.56 μJ/cm2, and modulation depth of 3.14%. The fabricated BP/PDMS SA was integrated into a ring cavity erbium-doped fiber laser (EDFL). By adjusting the polarization states of the circulating light in the cavity, the EDFL produced an optical spectrum with Kelly sidebands to prove the generation of conventional soliton (CS). The output pulse had a central wavelength of 1560.18 nm, 3-dB spectral width of 5.92 nm, pulse duration of 724 fs, repetition rate of 6.53 MHz, and time bandwidth product (TBP) of 0.53 showing the SA capable of generating ultrashort pulses. Next, black phosphorus layers (BPLs) and black phosphorus quantum dots (BPQDs) were synthesized from bulk BP through liquid phase exfoliation method. The findings from high resolution transmission electron microscopy and atomic force microscopy suggested BPLs were in diameter range from 69 – 362 nm and thickness range of 42 – 62 nm. Whereas BPQDs displayed a lateral size of 2.92 ± 0.37 nm as analyzed from the TEM image. Then, BPLs/PMDS and BPQDs/PDMS composite SA were fabricated following the same procedure as implemented for BP/PDMS SA. These fabricated SAs were inserted into the same EDFL cavity to study their pulse performance characteristics. The transmission loss of BPLs/PDMS coated microfiber was 2.57 dB whereas BPQDs/PDMS composite coated microfiber was 2.12 dB at 1550 nm, respectively. The nonlinear absorption of BPLs/PDMS composite coated microfiber possesses saturation fluence of 9.22 μJ/cm2, modulation depth of 3.5%, and two-photon absorption (TPA) of 5.3 x 10-3 cm2/μJ while the BPQDs/PDMS coated microfiber exhibited saturation fluence of 18.47 μJ/cm2, modulation depth of 2.12%, and TPA coefficient of 9.1 x 10-3 cm2/μJ. The nonlinear optical absorption response shows that due to different size of BPs, both SAs showed different TPA characteristics that caused CS to noise-like pulse (NLP) operation at different pump powers. In the CS operation, BPLs/PDMS composite SA generated 837 fs which was better in pulse duration compared to 1.11 ps of BPQDs/PDMS composite SA. Besides that, BPLs-SA had the lowest TBP value (0.39) among other structures BP-SAs which indicated the pulse was slightly chirped. However, in the NLP operation, BPQDs-SA showed shortest pulse generation at 152 fs due to strong TPA characteristic. Overall, the results validate the reliability of the proposed method to understand the effect of different BP/PDMS structures on microfiber based SAs for ultrashort pulse generation.